INFLUENCE of ovarian cycles on body composition using MFBIA - Poonam Khalsa, Er.; Jayanand Manjhi, Dr. (International Journal of Engineering and Technology, 2019)
Multi- Frequency Bioelectrical Impedance Analysis (MFBIA) is a technique used to estimate the body composition. MFBIA helps to evaluate the water and fat percentage in the body. In MFBIA, different frequencies (0, 50, 100, 200 to 500 kHz) are used to evaluate Fat Free Mass (FFM), Total Body Water (TBW), Intracellular Water (ICW) and Extracellular Water (ECW) content. The main objective of the study is to evaluate the outcome of the ovarian cycle on the composition of the body, with the help of 720 MFBIA and 520 MFBIA. Experiments are conducted on forty-four college-aged women of appropriate age and body mass (Age=21.4 Â± 1.1 years; Body Mass Index = 24.4 Â± 3.8 kg/m2). Body compositions of the women are assessed using 720 MFBIA and 520 MFBIA analyzers during all the phases of ovarian cycle namely ovarian, follicular, early and late luteal phase. The research study indicates that 720 MFBIA is better tool than 520 MFBIA to study the effect of ovarian cycles on body compositions.Â Â